Analisis Sentimen Berdasarkan Opini dari Media Sosial Twitter terhadap “Figure Pemimpin” Menggunakan Python - Mahawardana, Putu Pasek Okta; Sasmita, Gusti Arya; Pratama, I Putu Agus Eka (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 3 No 1 (2022): JITTER, Vol.3, No.1, April 2022DO - 10.24843/JTRTI.2022.v03.i01.p17, 2022)
Social media is a medium used to socialize and exchange information by its users using the internet. There are many benefits of social media, several uses of social media such as meeting new friends, knowing sports, economics, tourism information and also for political matters. One of them is the figure of the leader of the presidential candidate for 2024, so the writer wants to know what information can be taken from public opinion on Twitter social media about the figure of the leader of the presidential candidate for 2024. This problem can be overcome by conducting research in the field of Sentiment Analysis, which is a a field of research that focuses on the computational study of opinions, behavior, and emotions towards an entity as outlined in the form of text. This study was conducted to find out how the results of sentiment analysis related to public response to the news of the 2024 presidential candidate and classify them into three classes, namely positive, negative, and neutral using Python. The results of this study are positive class sentiments of 21.6% with a total of 108, neutral by 78% with a total of 390 and negative by 0.2% with a number of 2. It can be concluded that this study tends to be neutral.